2014
DOI: 10.1002/app.40738
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline fungal degradation of oxidized polyethylene in black liquor: Studies on the effect of lignin peroxidases and manganese peroxidases

Abstract: High-molecular-weight polyethylene is resistant to natural environmental degradation for its crystalline, hydrophobic structure. In this study, waste polyethylene bags are chemically oxidized at 80 C for 5 days by potassium dichromate solutions of various concentrations along with sulfuric acid. Absorbance peaks of carbonyl and carboxylate ions in the Fourier transform infrared spectroscopy spectra and formation of amorphous phase from crystalline one as indicated in X ray diffraction studies of oxidized polye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…The concentrated culture supernatants of lignocellulose‐degrading Streptomyces species containing LiP activity were reported to degrade the PE fraction of a heat‐treated plastic blend (Pometto et al ., ). Similarly, the extracellular LiP and MnP of Phanerochaete chrysosporium MTCC‐787 were reported to degrade 70% of a preoxidized high molecular weight PE sample within 15 days of incubation (Mukherjee and Kundu, ).…”
Section: Enzymatic Degradation Of Plastics With Carbon‐carbon Backbonesmentioning
confidence: 95%
“…The concentrated culture supernatants of lignocellulose‐degrading Streptomyces species containing LiP activity were reported to degrade the PE fraction of a heat‐treated plastic blend (Pometto et al ., ). Similarly, the extracellular LiP and MnP of Phanerochaete chrysosporium MTCC‐787 were reported to degrade 70% of a preoxidized high molecular weight PE sample within 15 days of incubation (Mukherjee and Kundu, ).…”
Section: Enzymatic Degradation Of Plastics With Carbon‐carbon Backbonesmentioning
confidence: 95%
“…Comparing weight loss figures in the studies reviewed (Table S1 & Table S2) does, however, indicate increased LDPE biodegradation over HDPE, enhancement of biodegradation following a PT step (Balasubramanian et al, 2014;Sheik et al, 2015), and variation in biodegradative capacity within and between genera (Alsherehrei, 2017;Muhonja et al, 2018;Sáenz et al, 2019). In a small subset of studies, considerable (>40%) weight losses have been reported over 15-90 days (Mukherjee and Kundu, 2014;Raut et al, 2015;Alsherehrei, 2017;Paço et al, 2017).…”
Section: (Bio)fragmentationmentioning
confidence: 99%
“…This article is protected by copyright. All rights reserved however, the activities of LiP, MnP, and laccase have all been associated with the biodegradation of PE by fungal species (Iiyoshi et al, 1998;Mukherjee and Kundu, 2014;Kang et al, 2019;Zhang et al, 2020) and some efforts at enhancing their action have been made. All three enzymes most typically attack the phenolic subunits of lignin but may also attack non-phenolic subunits -which PE most closely resembleswith the addition of mediators (Datta et al, 2017;Kumar and Chandra, 2020).…”
Section: Accepted Articlementioning
confidence: 99%
“…Owing to the higher bond energy of its carbon–carbon single bonds (330–370 kJ mol −1 ), 3 polyethylene requires functionalization before plastic-degrading enzymes can be used to catalyze its degradation reaction. 4 Current pretreatment methods mainly include the use of ultraviolet (UV), 5 strong acid, strong alkali, or inorganic oxidant treatment, 6 and the functional groups hence generated are mainly hydroxyl, carbonyl, and carbon–carbon double bonds. 7 It has been reported that the above pretreatment can lead to some oxidoreductases degrading the polyethylene.…”
Section: Introductionmentioning
confidence: 99%
“…7 It has been reported that the above pretreatment can lead to some oxidoreductases degrading the polyethylene. For example, laccase (Lac)-degraded UV oxidizes polyethylene, with a loss of M w of about 20%, 8 lignin peroxidase (Lip) and manganese peroxidase (Mnp) degraded K 2 Cr 2 O 7 oxidizes polyethylene in black liquor as medium, 6 and latex cleating protein (Lcp) catalyzed the UV oxidation of polyethylene, with a loss of M w of about 42.02%. 9 Although the above pretreatment methods effectively improve the degradation efficiency of biological enzymes, 10 no research has been conducted to clarify the mechanism by which they degrade polyethylene by using oxygen-containing groups.…”
Section: Introductionmentioning
confidence: 99%